In situ structural changes of crystalline and amorphous cellulose during slow pyrolysis at low temperatures - Leng, E.; Zhang, Y.; Peng, Y.; Gong, X.; Mao, M.; Li, X.; Yu, Yun (Elsevier Ltd, 2018)
This study reveals the evolution of functional groups during slow pyrolysis of crystalline and amorphous cellulose at low temperatures, using in situ diffuse reflectance infrared Fourier transform (DRIFT) spectroscopy combined with two-dimensional perturbation correlation infrared spectroscopy (2D-PCIS). During cellulose pyrolysis, although the inter-molecular hydrogen bonds are slightly stronger, both intra- and inter-molecular hydrogen bonds can break at low temperatures (i.e., > 120 °C), leading to the formation of free hydroxyl. Due to the weakened hydrogen bonds in cellulose, dehydration reactions firstly take place to produce saturated carbonyls, at a lower temperature (i.e., 240 °C) for amorphous cellulose. At increased temperatures (i.e., > 270 °C), the hydrogen bonds in cellulose reduce more significantly, promoting the decomposition of glucopyranose rings to form double bonds (i.e., carbonyls, carboxyls and conjugated alkenes). Compared to those for amorphous cellulose, the hydrogen bonds in crystalline cellulose are more stable, thus protecting the functional groups (i.e., –CH groups, glycosidic bonds and glucopyranose rings) from rapid disruption.